Antimicrobial potential and stability of Lactobacillus acidophilus-derived bacteriocins against multidrug-resistant common foodborne pathogens - Md Mahmudul Hasan; Fahmida Jahan Fahim; Sohel Rana; Sodor Uddin; Musammat Fathema Sultana Tonny; Sanchita Sarkar; Kazi Zinnah; Ferdaus Mohd Altaf Hossain (Applied Food Research)
The global rise of multidrug-resistant (MDR) pathogens requires alternative solutions of antimicrobials, particularly in maintaining food safety and preventing pathogen-associated AMR in clinical settings. In this study, we have collected a total of forty eight (n=48) commercial yogurt to isolate and molecularly characterized L. acidophilus, followed by the production of cell free supernatants (CFS), and purify the bacteriocin using ammonium sulfate (60-80%) precipitation and dialysis. Then, we have checked the efficacy and stability of bacteriocin in diverse environment, followed by their antimicrobial activity against our previously identified Escherichia coli, Salmonella enteritidis, Klebsiella pneumoniae, and methicillin-resistant Staphylococcus aureus (MRSA) from different foods. The bacteriocin demonstrated substantial activity, with MIC values ranging from 3–10 µg/mL of 0.5 MacFarland of targeted bacterial concentration, and stability under diverse environmental conditions. Our L. acidophilus-derived bacteriocins demonstrated effective at diverse pH, temperature, bile salts, and UV exposure. Particularly, the best affectivity and stability demonstrated at pH 5, bile salt concentration 0.1%, temperature 30°C, and UV exposures for 15 min. In comparative analysis, though vancomycin was found to be more effective than our harvested bacteriocin against the targeted bacteria, however, the potential of bacteriocin as natural antimicrobial agents was also convincible. The findings recommend L. acidophilus- derived bacteriocin as a promising alternative in combating MDR foodborne bacteria. Further researches are crucial to elucidate the mechanisms, cytotoxicity, and in-vivo efficacy of this bacteriocin for strengthening the commercial and therapeutic applications.